2008
DOI: 10.1007/s11065-008-9065-y
|View full text |Cite
|
Sign up to set email alerts
|

State of Multicultural Neuropsychological Assessment in Children: Current Research Issues

Abstract: Scientific attention to cultural considerations in child neuropsychological assessment has not developed parallel to the focus these issues have received in adult and elderly neuropsychological assessment. There are limited data on the presence, magnitude, etiology, and implications of culture-related differences in cognitive test performance among children. This preliminary report reviews the available empirical literature on the current state of multicultural neuropsychological assessment in children. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…Finally, cultural differences and contextual understanding of neurocognitive function may impact neurocognitive testing, bias results, and lessen the validity of findings. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, cultural differences and contextual understanding of neurocognitive function may impact neurocognitive testing, bias results, and lessen the validity of findings. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a significant amount of research in cross-cultural neuropsychology is found from the 21 st century (e.g., Arias et al, 2019;Brickman, Cabo, & Manly, 2006;Byrd et al, 2008;Chiao et al, 2017;Duggan, 2019;Duggan et al, 2019;Fernández, & Abe, 2018;Garratt & Kelly, 2007;Golden & Thomas, 2000;Jacobs et al, 1997;Manly, 2008;Melikyan, Puente, & Agranovich, 2020;Nielsen et al, 2018;Nikolaou & Constantinidou, 2019;Pedraza, & Mungas, 2008;Puente et al, 2000;Rosselli, & Ardila, 2003). Several neuropsychology journals express their interest in publishing papers dealing with cultural issues in neuropsychology, including the Journal of Clinical and Experimental Neuropsychology, Archives of Clinical Neuropsychology, and Applied Neuropsychology.…”
Section: The Origins Of Cross Cultural Neuropsychologymentioning
confidence: 99%
“…That is why cross-cultural studies present great interest to developmental psychology as they make it possible to evaluate and compare how various environmental factors resulting from specific features of cultures under investigation, on the one hand, and individual differences, on the other, influence the formation of executive functions. Given the obvious significance and usefulness of such studies many scientists have to note that there has been insufficient empirical research in investigating cultural differences in children's performance of cognitive regulation tasks (Byrd et al, 2008;Han et al, 2013). As a result, the present study was devoted to the examination of the developmental features of executive functions in preschool children belonging to two most wide-spread cultures -Russian and Tatarpresent on the territory of the Russian Federation, and, in particular, in its largest centres (Moscow and Kazan).…”
Section: Introductionmentioning
confidence: 99%